Customer-Centered Design Approach to Improve E-Commerce Web Site Usability - Syahrul Nizam, Junaini; Jonathan, Sidi (Centre for Academic Information Services, UNIMAS, 2007)
In the development process of e-commerce online store, the attributes of the store and its product display is very important. The fundamental problem that motivates this study is to find the factors that determine customer acceptance of virtual stores especially related with the product display. We argue that from the user experience point of view the critical success factors of highly usable e-catalogs are not so well understood. Our framework consists of the usability factors such as simplicity, attractiveness, effectiveness, product image, website information, interactivity, navigation, categorization and product details. Through the experimental study, three different studies were carries out. First, the features of three airlines web sites in Malaysia, which are AirAsia (www.airasia.com), Malaysia Airlines (www.mas.com.my) and StarAir (www.starair-online.com) have been analyzed. In this experiment, we present a theoretical framework that highlights the importance of (1) convenient booking flow; (2) efficiency; (3) ease of use; (4) interactivity; and (5) attractiveness to attract the customers. Furthermore, to investigate the level of aesthetics, attractiveness and interactivity, this research studied three other sites: jcpenny.com, victoriassecret.com and adidas.com. The third study involved another nine sites from three product categories such as handicrafts and cosmetics. The result of this research provides a basis for better user experience assessment of the e-commerce web sites. We end with suggestions for better e-commerce site usability based on customer centered design approach.